2024
DOI: 10.1108/jd-10-2023-0200
|View full text |Cite
|
Sign up to set email alerts
|

Contested imaginaries: workfinding information practices of STEM-trained immigrant women in Canada

Nadia Caidi,
Saadia Muzaffar,
Elizabeth Kalbfleisch

Abstract: PurposeThis pan-Canadian study examines the information practices of STEM-trained immigrant women to Canada as they navigate workfinding and workplace integration. Our study focuses on a population of highly skilled immigrant women from across Canada and uses an information practice lens to examine their lived experiences of migration and labour market integration. As highly trained STEM professionals in pursuit of employment, our participants have specific needs and challenges, and as we explore these, we con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“…From an information studies perspective, the two-year study pays attention to how the women accessed information about immigration and job prospects and problem-solved their way through the upheaval of starting new personal and professional lives in Canada. Caidi et al (2024) report the findings of the two-year study that revealed "challenges associated with employment-seeking and workplace integration for STEM-trained women" (p. 14 of 23). In this article, however, we focus on making the animated film "We Were Here All Along: Canada's Failed Promise to Immigrant Women in STEM," which resulted from the research findings of the two-year study.…”
Section: Introductionmentioning
confidence: 99%
“…From an information studies perspective, the two-year study pays attention to how the women accessed information about immigration and job prospects and problem-solved their way through the upheaval of starting new personal and professional lives in Canada. Caidi et al (2024) report the findings of the two-year study that revealed "challenges associated with employment-seeking and workplace integration for STEM-trained women" (p. 14 of 23). In this article, however, we focus on making the animated film "We Were Here All Along: Canada's Failed Promise to Immigrant Women in STEM," which resulted from the research findings of the two-year study.…”
Section: Introductionmentioning
confidence: 99%